2018
DOI: 10.3390/polym10030227
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Application of Phosphorene as a Flame Retardant

Abstract: Black phosphorene-waterborne polyurethane (BPWPU) composite polymer with 0.2 wt % of black phosphorene was synthesized. Scanning electron microscopy (SEM) was used to observe the morphology of phosphorene in polyurethane matrix, which indicated that the phosphorene distributes uniformly in the PU matrix. The flammability measurements were carried out to investigate the flame-resistant performances of phosphorene, which indicated that phosphorene could effectively restrict the degradation of the PU membrane. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Compared with volatile white phosphorus and amorphous red phosphorus, BP also exhibits higher thermal stability and phase-dispersion, which could improve the flame-retardant performance and reduce damage to the mechanical properties of the polymers. In previous research, we reported that BP can effectively enhance the thermal stability and fire resistance of polymers [ 21 ]. Yuan Hu, et al synthesized the BP/carbon nanotube composite and demonstrated its synergistic flame retardant performance for epoxy resin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with volatile white phosphorus and amorphous red phosphorus, BP also exhibits higher thermal stability and phase-dispersion, which could improve the flame-retardant performance and reduce damage to the mechanical properties of the polymers. In previous research, we reported that BP can effectively enhance the thermal stability and fire resistance of polymers [ 21 ]. Yuan Hu, et al synthesized the BP/carbon nanotube composite and demonstrated its synergistic flame retardant performance for epoxy resin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the performance of the FSPUs as flame retardant materials, microscale combustion calorimeter (MCC) based on oxygen consumption calorimetry was conducted by pyrolysis combustion flow calorimetry (PCFC) [37]. MCC can quickly and easily provide the key flammability parameters of materials, such as peak heat release rate (pHRR), total heat released (THR) and temperature at pHRR (T p ) [37,38]. The MCC data of PUs with different contents of ACP were presented in Table 3.…”
Section: Flame Retardant Evaluationmentioning
confidence: 99%
“…Reproduced under the terms and conditions of the Creative Commons CC BY 4.0 license. [ 261 ] Copyright 2018, The Authors, published by MDPI. f) Atomic force microscopy image of a single‐layer phosphorene crystal.…”
Section: Structure Of Phosphorenementioning
confidence: 99%